Teachers’ Critical Reflections on the New Normal Philippine Education Issues: Inputs on Curriculum and Instruction Development - Aljon Delmo Galang (International Journal of Social Learning (IJSL), 2021)
Due to the COVID-19 pandemic, the Philippine educational landscape is greatly affected. This education issue concerns the country's curriculum and instruction (CIN), covering students' learning, delivery modalities, competencies, teachers' characteristics, and community involvement. Nonetheless, the CIN must be developed, considering the students, teachers, community, and the pressing challenges in the teaching-learning process, promoting quality education while considering the pandemic, by looking into teachers' perspectives. This qualitative research used content analysis to derive insights from the critical reflections of sixteen (16) teacher participants. It aims to present the participants' reflections on the New Normal education issues, leading to curriculum and instruction development inputs. Furthermore, the emerging themes are (a) essentiality and feasibility in choosing learning competencies; (b) good quality, flexibility, sustainability, and safety in choosing learning modalities; (c) learning materials' alignment, sufficiency, and proper distribution; (d) devotion, adaptability, and helpfulness of teachers; (e) reaching out students and task individualization; and (f) leadership and involvement needed to achieve success in education. Moreover, the findings suggest that the New Normal classroom requires a curriculum and instruction, teacher, leadership, and involvement adaptive and flexible of the changing and multifaceted educational landscape brought by the persisting disease.